Penetapan Kadar Cemaran Logam Kadmium dalam Jamu Liver Sediaan Kapsul Secara Inductively Coupled Plasma–Optical Emission Spectrometry - Lusi Veronika; Ruth Elenora Kristanty; Ai Emalia Sukmawati; Siti Nur Aliza Fauziah (Journal Clinical Pharmacy and Pharmaceutical Science, 2024)
Heavy metal contamination can cause health problems such as impaired brain, liver, kidney, lung and muscle function. One of the quality and safety checks for herbal medicine is heavy metal contamination analysis. Natural medicines can be contaminated from agriculture, production and distribution processes. Therefore, the test was carried out to determine the level of cadmium metal contamination in liver herbs in capsule preparations by Inductively Coupled Plasma - Optical Emission Spectrometry. The test aims to determine whether the capsule herbal liver samples meet the requirements for cadmium heavy metal levels in accordance with the Regulation of the Food and Drug Administration of the Republic of Indonesia Number 29 of 2023. This test uses samples of liver herbal medicine in capsule dosage form. The results of heavy metal contamination results were positive for cadmium with an average level of 0.4031 mg/kg. So it can be concluded that the sample does not meet the requirements (TMS) cadmium metal contamination levels.